All Days 2008
DOI: 10.2118/115042-ms
|View full text |Cite
|
Sign up to set email alerts
|

Oil Production and Water-Cut in Naturally-Fractured Vuggy Reservoirs

Abstract: Naturally fractured oil reservoirs with vugs of size over 5 meters in diameter are few in the world. We developed a method to correlate the decrease in oil production and the increase in water cut. Production data from Tah oil reservoir (China) with big size vugs and high-density fractures were used to test the approach. It was found that the oil production decline and the water cut increase were coupled closely in many wells from this naturally fractured vuggy oil reservoir. The oil production was characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Ivanova (2008) found regularities and confirmation watercut by means of analytical and numerical calculations. Li et al (2008) developed a method to correlate the decrease in oil production and the increase in water cut. It was found that the oil production decline and the water cut increase were coupled closely in many wells from this naturally fractured vuggy oil reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Ivanova (2008) found regularities and confirmation watercut by means of analytical and numerical calculations. Li et al (2008) developed a method to correlate the decrease in oil production and the increase in water cut. It was found that the oil production decline and the water cut increase were coupled closely in many wells from this naturally fractured vuggy oil reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Foi citado que a recuperação de óleo deste campo teve um incremento de 33% com a implantação da injeção de água. Li et al (2008) cita que o reservatório Tah (reservatório fraturado e vugular localizado na China) tem rápido declínio da pressão e aumento acentuado do corte de água assim que a irrupção de água atinge os poços.…”
Section: Métodos De Recuperação Em Reservatórios Fraturadosunclassified